2003
DOI: 10.1086/374623
|View full text |Cite
|
Sign up to set email alerts
|

Classical and Latent Class Analysis Evaluation of Sputum Polymerase Chain Reaction and Urine Antigen Testing for Diagnosis of Pneumococcal Pneumonia in Adults

Abstract: Diagnosis of pneumococcal pneumonia is complicated by the lack of a diagnostic reference standard that is highly sensitive and specific. Latent class analysis (LCA) is a mathematical technique that relates an unobserved ("latent") infection to multiple diagnostic test results by use of a statistical model. We used classical analysis and LCA to evaluate the sensitivity and specificity of blood culture, sputum Gram stain, sputum polymerase chain reaction (PCR), and urine antigen testing for diagnosing pneumococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 40 publications
3
49
1
2
Order By: Relevance
“…In a recent study, Butler et al used latent class analysis to determine the sensitivity and specificity of blood cultures (14) and confirmed previous results.…”
Section: Optimal Samples For Detection Of Respiratory Pathogens Invassupporting
confidence: 59%
See 2 more Smart Citations
“…In a recent study, Butler et al used latent class analysis to determine the sensitivity and specificity of blood cultures (14) and confirmed previous results.…”
Section: Optimal Samples For Detection Of Respiratory Pathogens Invassupporting
confidence: 59%
“…When a purulent sample was available, the Gram stain gave a presumptive diagnosis in 175/210 cases (80%). The studies by Butler et al and Miyashita et al confirmed these results (14,70).…”
Section: Using 10mentioning
confidence: 73%
See 1 more Smart Citation
“…The case is especially noteworthy for community-acquired pneumonia (CAP), for which positivity rates are very low and blood cultures cannot be used to direct treatment (3). The results of sputum Gram stain and culture are positive for 31 to 68% and 28 to 86% of patients with pneumococcal pneumonia who can produce sputum, respectively (8,21,43,46,54), while the test for pneumococcal urine antigen is positive for about 70 to 87% of patients (8,22,61,63), with all values being highly dependent on previous antibiotic treatment.Molecular methods for pathogen identification are appealing since, in principle, the results should not depend on the amount of pathogen present in the sample, identification defined by DNA can be highly specific, and noncultivable pathogens can be detected (18,44). The results can be made available within hours of a patient's presentation with an infection, during the time window that allows the direction of early antibiotic treatment.…”
mentioning
confidence: 99%
“…The case is especially noteworthy for community-acquired pneumonia (CAP), for which positivity rates are very low and blood cultures cannot be used to direct treatment (3). The results of sputum Gram stain and culture are positive for 31 to 68% and 28 to 86% of patients with pneumococcal pneumonia who can produce sputum, respectively (8,21,43,46,54), while the test for pneumococcal urine antigen is positive for about 70 to 87% of patients (8,22,61,63), with all values being highly dependent on previous antibiotic treatment.…”
mentioning
confidence: 99%